Moringa oleifera Lam.: A comparative survey on consumer knowledge, usage, attitude and belief in Africa and India - (:unkn) unknown (My University, 2022)
Native to India, Moringa oleifera Lam. is a plant with high nutritional value, which is now grown across the world, especially in tropical and subtropical regions. This study determined the knowledge, consumption, attitudes and beliefs toward Moringa oleifera in some African countries (Nigeria, Ghana, and South Africa) and in India to gain a better understanding of why this plant is widely consumed in India but less so in Africa. An online survey was conducted using a snowball sampling procedure with 258 respondents who are consumers of Moringa (124 are Indians and 134 are Africans; 54% are Male and 46% are Female). We hypothesized that the differences in patterns of Moringa consumption in India and Africa might be due to differences in knowledge, attitudes and beliefs towards Moringa. In particular, we expected Indian respondents to have a better knowledge and more positive attitudes and beliefs towards Moringa than African respondents. Based on our study sample, we observed differences in terms of knowledge and consumption of Moringa between Indian and African respondents. However, these differences could not be explained in terms of beliefs and attitudes: No significant difference was found between African and Indian respondents’ beliefs towards Moringa. Having positive attitudes and beliefs is not enough to change Moringa consumption behavior. Past behavior seems to be a better predictor of Moringa consumption behavior. As Moringa is not yet anchored in African families and cultural practices, especially in South Africa, providing only nutritional and health information is not enough to promote Moringa consumption in Africa. A better option would be to increase the familiarity of Moringa by incorporating it into familiar local foods with a high satiating power. Family also seems to be an important driver of Moringa consumption that needs to be taken into account.
Keywords: African Research